The Liberty Line : The Legend of the Underground Railroad - Gara, Larry (Book collections on Project MUSE., 1996)
Organization spirited floods of slaves away from the South. In contrast to that legend, the slaves themselves had active roles in their own escapes from slave states. They carried out their runs to the North, receiving aid only after they had reached territory where they still faced return under the Fugitive Slave Law. Thus, The Liberty Line places fugitive slaves in their rightful position: the center of their struggle for freedom.